‘Facebook and Google care deeply about journalism’? Mapping audience-based monetization projects and the impact on journalistic practices and values - Papa, Venetia; Kouros, Theodoros (My University, 2022)
Facebook and Google launches in 2017 and 2020, ‘Google News Initiative’ and ‘Facebook Journalism Project’ respectively to provide cutting-edge tools to help journalists understand and connect with their users, improve their products and power their technological infrastructure. This goes in line with the strategy of ‘infrastructuralization’ applied by Google and Facebook to centralize international flows and reinvent relationships between diverse publics (Plantin et.al., 2018). Along with this, news organizations have been forced to reinvent the ways by adapting their editorial decisions, shaping their forms in search of alternatives by which they can monetize their news stories through a ‘platform native strategy’. Thus, technological platforms are seen as ‘digital intermediaries’ with specific business models where data-power processes tackle the production, monetization and visibility of journalistic content. While this is evident, publishers and news organizations might reinvigorate their institutional practices and values to priorities and values of the platforms in a process of “institutional isomorphism” (Caplan and Boyd, 2018). Whereas significant empirical and theoretical work has been focused on the promises of technology on journalism per se, little is known about innovation projects that take place within technological corporations and are vastly applied in news organisations. Thus, little is known about human aspects of technological approaches in influencing journalistic identities.
Keywords: Facebook; Google; journalism